Quark-gluon plasma phenomenology from the lattice - Gert Aarts (Journal of Physics: Conference Series, 2013)
The FASTSUM Collaboration has calculated several quantities relevant for QCD studies at non-zero temperature using the lattice technique. We report here our results for the (i) interquark potential in charmonium; (ii) bottomonium spectral functions; and (iii) electrical conductivity. All results were obtained with 2+1 flavours of dynamical fermions on an anisotropic lattice which allows greater resolution in the temporal direction.